Migration, Trade and Unemployment - Benedikt Heid; Mario Larch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
A source of anxiety of policy makers and the public in general is the detrimental impactof globalization and immigration on unemployment. The transitory restrictions forworker migration after the EU enlargements of 2004 and 2007 exemplify the supposednegative effect of immigration on labor markets. This paper aims to identify the effectsof immigration alongside trade on unemployment taking into account the substitutabilityof worker and goods flows. We use data from 24 OECD countries over the periodfrom 1997 to 2007 and employ instrumental variables fixed effects and dynamic panelestimators in order to account for unobserved heterogeneity as well as the potentialendogeneity of migration flows and the high persistence of unemployment. We find asignificant negative effect of immigration on unemployment on average.
Keywords: F22; F16; C23; C26; F15; 330; Migration; unemployment; international trade; fixed effects instrumental variable panel estimators; dynamic panel estimators; Internationale Wanderung; Internationale Arbeitsmobilität; Globalisierung; Arbeitslosigkeit; Beschäftigungseffekt; OECD-Staaten; EU-Erweiterung; Osteuropa